Hydrolysis of a carbamate triggered by coordination of metal ions. Issue 34 (10th August 2022) - Fernández-Fariña, Sandra; Martínez-Calvo, Miguel; Romero, María J.; Seco, José M.; Zaragoza, Guillermo; Pedrido, Rosa; González-Noya, Ana M.
Abstract : The coordination of metal ions to a carbamate ligand triggers its hydrolysis, which ends up in self-immolation of the complex releasing new metal species, a pendant molecule (A) and CO2 . Abstract : The mechanism of carbamate activation promoted by different metal ions has been explored in this work. The reaction of the carbamate ligand H2 L with chloride metal salts (M = Ni, Cu, Zn, Cd) leads to the coordination of the metal ions to the ligand, causing hydrolysis of the systems. This self-immolation process results in mononuclear dihydrazone complexes, carbon dioxide and the release of alcohol species from the pendant groups of the carbamate ligand. The conditions under which this process occurs have been studied in detail.